PENGGUNAAN MEDIA KGW (KARTON GAMBAR WAYANG) PADA PEMBELAJARAN TEMATIK KELAS V DI SDN PENDEM II - Al Fath, Ayatullah Muhammadin; Muslim, Aji Heru (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2022)
This study aims to describe the cardboard wayang media in thematic learning in order to prevent student boredom and to introduce wayang media as the cultural heritage of the Indonesian nation. The method used in this research is a descriptive qualitative approach. The research was carried out in the odd semester of 2021/2022. The data collection techniques used interviews, observations and documentation. Interviews were addressed to educators and students. Observations were carried out to find out how the implementation of thematic learning for class V at SD N Jetak II was carried out. The findings before using KGW media (carton pictures puppet students are less interested in learning and easily feel bored so that learning outcomes are less effective. The result of the study showed that after using the KGW media (carton puppet pictures) students were more active in participating in learning and were not easily bored and students learning achievement improved better. The use of KGW learning media (carton puppet pictures) aims to minimize the use of plastic and increase student creativity at SD N Pendem II. So that KGW deserves to be used as an alternative to achieve effective learning.